Value-added ingredients and enrichments of beverages - Grumezescu, Alexandru Mihai; Holban, Alina Maria (Science of beverages ;, 2019)
Value-Added Ingredients and Enrichment of Beverages, Volume Fourteen in The Science of Beverages series, takes a multidisciplinary approach in addressing what consumers demand in natural beverages. This in-depth reference covers both natural and unnatural ingredients and explains their impact on consumer health and nutrition. Sweeteners, vitamins, oils and other natural ingredients to improve beverages are included. The book addresses some of the most common enrichments used in the industry, including those with biomedical and nutritional applications. This volume will be useful to anyone in the beverages industry who needs a better understanding of advances in the industry. --